JUDICIALIZATION OF PUBLIC HEALTH POLICIES AND JUDICIAL REVIEW OF STATE OMISSION: CRITERIA FOR ENFORCING THE FUNDAMENTAL RIGHT TO HEALTH IN ELECTIVE PROCEDURES - Leonardo Soares de Sousa (Artefactum - revista de estudos interdisciplinares, 2026)
This article analyzes the role of the Judiciary in enforcing the fundamental right to health, with special attention to claims involving elective surgical procedures within the Brazilian Unified Health System. The research problem is: under what conditions may judicial intervention in public health policies be considered legitimate without violating the separation of powers, equality among system users, and technical criteria for administrative regulation? The general objective is to examine the limits and possibilities of judicial action in cases of state omission or excessive delay in the provision of public health services. The specific objectives are to understand the fundamental nature of the right to health, discuss the enforceability of social rights and identify legal and institutional criteria capable of rationalizing judicialization of healthcare. The research adopts a qualitative approach and deductive method, based on bibliographic review and documentary analysis of the Brazilian Constitution of 1988, Law n. 8,080/1990, the Brazilian Code of Civil Procedure, precedents of the Federal Supreme Court and the Superior Court of Justice, as well as normative acts and interpretive guidelines. The article concludes that the Judiciary should not ordinarily replace public administration in policy-making or in the organization of waiting lists. However, judicial intervention is legitimate when arbitrary denial, unjustified omission, excessive delay, lack of transparency, risk of clinical deterioration, or noncompliance with an existing public policy is demonstrated. In such cases, judicial decisions must observe technical criteria, specialized support, proportionality, equality, and the lowest possible systemic impact.